Regras de sintonia do preditor de Smith filtrado simplificado para sistemas de primeira ordem com atraso - Freitas, Felipe Câmara de (2025)
This paper proposes tuning rules for the Simplified Filtered Smith Predictor for first- order systems with transport delay. These rules are derived from the robust stability condition of the controller and provide the minimum desired parameter to ensure stability and fast rejection of constant disturbances. To achieve this, it is only necessary to provide the system gain, the pole, as well as the time delay along with its maximum uncertainty, and the control gain. Once the analytical form of these rules is obtained, the solutions to the involved transcendental equations are determined through an approximate or numerical method. A program for automatic calculation of the tuning parameter is developed to ease the designer's task. Finally, each rule is tested on the respective first-order systems through simulation and compared with other recent works in the literature. The results show that the proposed rules are effective in determining the value of the filter parameter that is small enough to ensure good performance in disturbance rejection while still ensuring the stability of the control system in the presence of uncertainty in the transport delay value.